2017
DOI: 10.3233/jbr-170154
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening and evaluation of phenolic antioxidant-linked anti-hyperglycemic functions of rabbit-eye blueberry (Vaccinium ashei) cultivars

Abstract: BACKGROUND: Higher consumption of phenolic-antioxidant rich berries have been associated with lower risks of chronic diseases, such as type 2 diabetes. In order to target for diet-based therapy it is important to screen and evaluate the right cultivars of berries with optimum phenolic antioxidants and associated anti-hyperglycemic functions. OBJECTIVE: Therefore, the primary objective of this study was to screen different rabbit-eye blueberry cultivars extracted in water and ethanol for their phenolic antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The same was observed by Cardeñosa and co-workers, where the genotype influenced the antioxidant capacity and the content of the three groups of phenolics in blueberry fruits [ 32 ]. In accordance of Sarkar and co-workers, the genotype versus environment interactions are most critical in the in vitro anti-diabetic-relevant functionalities of blueberry bioactives [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same was observed by Cardeñosa and co-workers, where the genotype influenced the antioxidant capacity and the content of the three groups of phenolics in blueberry fruits [ 32 ]. In accordance of Sarkar and co-workers, the genotype versus environment interactions are most critical in the in vitro anti-diabetic-relevant functionalities of blueberry bioactives [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the α‐amylase inhibitory activity was also found to be correlated with the antioxidant capacity of the blueberry extract (see Figure 6b) with a correlation coefficient r equal to .726. A previous study evaluated five different rabbit‐eye blueberry cultivars and showed that their α‐amylase inhibitory activity has a positive correlation with both phenolic content and antioxidant capacity (Sarkar et al., 2017). He et al obtained the highest r value (.485), among the relationships studied, for the correlation between α‐amylase inhibitory activity and total polyphenol content when investigating 22 fruit juices after in vitro gastrointestinal digestion (He et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…(3) y = Bottom + (Top − Bottom) ∕ 1 + 10 ( logIC50 − x ) × HillSlope , F I G U R E 5 The α-amylase (a) and tyrosinase (b) activity inhibition percentage versus the log of blueberry concentration; experimental data (dot), simulation (line) F I G U R E 6 Correlations of α-amylase inhibitory activity with TPC (a) and antioxidant capacity of blueberry extract (b) a correlation coefficient r equal to .726. A previous study evaluated five different rabbit-eye blueberry cultivars and showed that their α-amylase inhibitory activity has a positive correlation with both phenolic content and antioxidant capacity (Sarkar et al, 2017). He et al obtained the highest r value (.485), among the relationships studied, for the correlation between α-amylase inhibitory activity and total polyphenol content when investigating 22 fruit juices after in vitro gastrointestinal digestion (He et al, 2017).…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 99%
“…Tyrosinase is one of the key enzymes responsible for the biosynthesis of melanin, and its inhibition is considered the best strategy to treat epidermal hyperpigmentation problems [53]. Tyrosinase also causes browning of fruits and vegetables, leading to quicker degradation and deterioration of nutritional value [54]. The use of tyrosinase inhibitors has attracted great attention in the cosmetic and pharmaceutical industries due to their preventive effects in pigmentation disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The use of tyrosinase inhibitors has attracted great attention in the cosmetic and pharmaceutical industries due to their preventive effects in pigmentation disorders. This scenario demands deliberate action involving the use of enzyme-inhibitory compounds as an effective strategy [54].…”
Section: Discussionmentioning
confidence: 99%